Systematic Literature Review (SLR): Penggunaan Teknologi Dalam Pembelajaran Bahasa Untuk Siswa Tunanetra - Farah ‘Izzati Najlaa’; Fathimah Ghaida Nafisa; Nur Afifah April Yani; Siti Hamidah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Language is an important skill that must be learned to be able to do daily activities and adapt to the environment. Visually impaired children are not exempt from this problem, considering that technology in this century is essential and everywhere due to its convenience to use and the usage of technology that simplifies activities. Activities that are being done include learning. It is important for individuals who will later interact and teach children who have visual impairments, to keep up with news about the effectiveness of learning, one of which is knowing the role of technology in language learning for visually impaired children. This article is made using the systematic literature review research method to find out the role of technology in language learning for visually impaired children, what technology can be used for language learning for visually impaired children, and its effectiveness in learning. The technology that has the ability to read PDF text, convert sounds in various languages, convert visual information into audio, and learn through audio greatly facilitates the learning of blind children, whether it is language learning or learning in general. Technology that facilitates blind learning has a good effect in general on the visually impaired children, such as the building of self-confidence for the visually impaired children due to the increased ability of the visually impaired children to learn to identify their environment, the ability to be independent, less dependence on others, and increased communication skills due to language learning that becomes more accessible.